Penyuluhan Status Gizi Dewasa dan Lansia di Desa Sijantung Kecamatan Galang Kepulauan Riau - Siska Pratiwi; Roza Erda; Afif D Alba; Suci Fitriani Sammulia; Rastria Meilanda (Jurnal Informasi Pengabdian Masyarakat, 2024)
The counseling on the nutritional status of adults and the elderly in Sijantung Village, Galang District, Riau Islands, was conducted to enhance the community's knowledge about the importance of balanced nutrition for long-term health. The counseling session was held on August 14, 2024, at Posyandu Permata Hati, and attended by adult and elderly groups. The topics covered included nutritional needs at various stages of life and ways to maintain and improve nutritional status. The results of this activity showed a significant increase in participants' understanding of the importance of good nutrition and simple ways to achieve it in daily life. This counseling is expected to be the first step in improving the nutritional status of adults and the elderly in the village